Cross-modal reorganization of callosal connectivity without altering thalamocortical projections - Pallas, Sarah L. (The National Academy of Sciences, 1999)
Mammalian cerebral cortex is composed of a multitude of different areas that are each specialized for a unique purpose. It is unclear whether the activity pattern and modality of sensory inputs to cortex play an important role in the development of cortical regionalization. The modality of sensory inputs to cerebral cortex can be altered experimentally. Neonatal diversion of retinal axons to the auditory thalamus (cross-modal rewiring) results in a primary auditory cortex (AI) that resembles the primary visual cortex in its visual response properties and topography. Functional reorganization could occur because the visual inputs use existing circuitry in AI, or because the early visual inputs promote changes in AI’s circuitry that make it capable of constructing visual receptive field properties. The present study begins to distinguish between these possibilities by exploring whether the callosal connectivity of AI is altered by early visual experience. Here we show that early visual inputs to auditory thalamus can reorganize callosal connections in auditory cortex, causing both a reduction in their extent and a reorganization of the pattern. This result is distinctly different from that in deafened animals, which have widespread callosal connections, as in early postnatal development. Thus, profound changes in cortical circuitry can result simply from a change in the modality of afferent input. Similar changes may underlie cortical compensatory processes in deaf and blind humans.